Metastatic prostate adenocarcinoma to the brain - a clinicopathologic analysis of 21 cases - Namra Ajmal; Yutao Deng; Lawrence C. Kenyon; Mark T. Curtis; Mauro Dispagna; Joseph Izes; Li Li (BMC, 2024)
Abstract Background Brain metastasis from prostate adenocarcinoma (PCa) is rare, often leading to death within a year. Its infrequent occurrence and atypical histopathologic features contribute to lower consideration in the differential diagnosis of tumor brain metastasis. This study aims to assess the clinical characteristics and distinctive histopathologic features of metastatic PCa in the brain for timely and enhanced diagnostic accuracy. Design A retrospective search spanning 20 years (2003-2022) was conducted on our archives and identified 21 cases diagnosed as "metastatic prostate adenocarcinoma (mPCa)" in brain biopsies and resections. All existing slides were thoroughly reviewed to evaluate the histopathology of the mPCa. Result The mean age at presentation for brain metastasis was 70 years. Of 21 cases, 5 were dural-based lesions, 16 were true intraparenchymal metastases, including 2 sellar/suprasellar masses, 3 frontal, 3 temporal, 3 occipital, 1 cerebellum, and 4 involving multiple brain lobes. The average interval between initial diagnosis and brain metastasis was 90.75 months. Notably, brain metastasis was the initial presentation for one patient, while another patient, initially diagnosed with prognostic grade group (GG) 2 PCa in 1/12 cores, presented with isolated brain metastasis two years later. Architecturally, tumor cells were arranged in sheets or nests in most cases; however, four cases showed histologic cribriform patterns, and five displayed papillary architecture. Cytohistology varied from uniform monomorphic to highly pleomorphic cells with prominent nucleoli (8/19) and high mitotic activity. Interestingly, 1 case showed small round blue cell morphology, another had focal areas of rhabdoid and spindle cell differentiation, and 6 had cytoplasmic clearing. Almost half of the cases (47%) showed necrosis. Conclusion mPCa to the brain can present with variable histomorphology. Therefore, consideration of mPCa in the differential diagnosis of metastatic brain lesions, even with non-suggestive imaging, is imperative in male patients with or without a history of primary disease. Accurate and prompt diagnosis is crucial, given the recent advancements in treatment that have improved survival rates.